Analisis Penerimaan Pajak Kendaraan Bermotor di Badan Pendapatan Daerah Provinsi Sulawesi Utara - Brinca, Febriane; Elim, Inggriani; Suwetja, I Gede (GOING CONCERN : JURNAL RISET AKUNTANSI, 2024)
Taxes in Indonesia are divided into two, namely central taxes and regional taxes, one of which is regional tax revenue, namely Motor Vehicle Tax (PKB). Every year the recording of Motor Vehicle Tax (PKB) receipts does not always increase, due to the possibility of a lack of optimization efforts in tax vehicle receipts. This research aims to determine efforts to optimize motor tax vehicle revenue at the Regional Revenue Agency of North Sulawesi Province. The type of research used is descriptive qualitative. The results of the research show that every year in 2021-2023 the PKB revenue target always increases, but in reality Motor Vehicle Tax (PKB) revenue over the last 3 (three) years has not always reached the target and efforts to optimize Motor Vehicle Tax (PKB) revenue in North Sulawesi Province in 2021-2023 are carried out by The Regional Revenue Agency of North Sulawesi Province is carrying out intensification efforts, such as developing the Motor Vehicle Tax (PKB) payment system, improving human resources, carrying out door to door searches and making the payment system easier by collaborating with the post office and banks of North Sulawesi. Apart from that, extensification efforts were also carried out, such as collaborating with traffic police and dealers.